The formation mechanism of aluminum oxide tunnel barriers: Three-dimensional atom probe analysis - Petford-Long, A; Ma, Y; Cerezo, A; Larson, D; Singleton, E; Karr, B (2005)
Magnetic tunnel junctions have applications in a range of spin-electronic devices. The functional properties of such devices are critically dependant on the nanoscale morphology of the insulating barrier (usually only a few atomic layers thick) that separates two ferromagnetic layers. Here we report atomic-resolution three-dimensional visualization of magnetic tunnel junctions with an aluminum oxide barrier, using three-dimensional atom probe analysis and cross-sectional high resolution electron microscopy. Our results on barriers with a range of degrees of oxidation have enabled a mechanism for the oxidation to be proposed. Low oxidation times result in discrete oxide islands and further oxidation leads to a more continuous, but nonstoichiometric, barrier. Post-deposition annealing leads to an increase in the barrier area and near stoichiometric chemistry with evidence that oxidation proceeds along the top of grain boundaries in the underlying CoFe. Our three-dimensional visualization enables us to show that even perforated barriers (formed at shorter oxidation times) can have reasonable transport properties. © 2005 American Institute of Physics.